Blockchain Technology, Its Applications and Open Research Challenges. Issue 1 (August 2021) - Kaushal, Rajesh Kumar; Kumar, Naveen; Panda, Surya Narayan
Abstract: Blockchain is a technology that operates on distributed peer-to-peer network and is widely adopted by large number of organizations due to its attractive features such as highly secured, transparent, traceable, low transaction fee, no need of central authority and confidentiality. There are lot of confusions and myths regarding the blockchain technology as it is emerging technology and too complex in nature. This paper is aimed at revealing blockchain technology in depth along with its applications and open research challenges. The past published literature was reviewed to achieve the objectives. The study found that apart from cryptocurrency, blockchain is also suitable for other applications such as smart cities, supply chain, healthcare, smart transportation and authenticating IoT (Internet of Things) devices. This study is also disclosing various open research challenges such as scalability issues, huge power consumption and delay in completing transactions. This paper is also sharing the mitigation approaches and the future of blockchain with smart contracts.